2016
DOI: 10.31219/osf.io/ptf97
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Growth mindset is not associated with scholastic aptitude in a large sample of university applicants

Abstract: Implicit theories of intelligence have been proposed to predict a large number of different outcomes in education. The belief that intelligence is malleable (growth mindset) is supposed to lead to better academic achievement and students' mindset is therefore a potential target for interventions. The present study used a large sample of university applicants (N = 5,653) taking a scholastic aptitude test to further examine the relationship between mindset and achievement in the academic domain. We found that re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Research casts doubt on social priming (Gerber et al 2017;Pashler et al 2012) or the reality of power posing (Jonas et al 2017). And research questions the degree to which intelligence mindsets (Bahník and Vranka 2017) or stereotype threat (Finnigan and Corker 2016;Flore and Wicherts 2015) explain performance outcomes. Though these are but a few examples, and the issue requires a systematic review to properly address, the present research on implicit attitudes joins a trend that lends credence to view that it is the conscious rather than unconscious mind that often takes priority in determining behavior.…”
Section: Resultsmentioning
confidence: 99%
“…Research casts doubt on social priming (Gerber et al 2017;Pashler et al 2012) or the reality of power posing (Jonas et al 2017). And research questions the degree to which intelligence mindsets (Bahník and Vranka 2017) or stereotype threat (Finnigan and Corker 2016;Flore and Wicherts 2015) explain performance outcomes. Though these are but a few examples, and the issue requires a systematic review to properly address, the present research on implicit attitudes joins a trend that lends credence to view that it is the conscious rather than unconscious mind that often takes priority in determining behavior.…”
Section: Resultsmentioning
confidence: 99%
“…Despite evidence for links between growth mindsets and reduced psychological distress as well as active coping (Burnette et al, 2020), within an academic context, recent work questions the magnitude of impact on scholastic aptitude (e.g. Bahník & Vranka, 2017; Sisk et al, 2018) and within stigma‐relevant domains, research highlights the potential dark side of growth mindsets (Hooper et al, 2018; Hoyt & Burnette, 2020).…”
Section: Metaphorical Thinkingmentioning
confidence: 99%
“…In recent years, a growth mindset has gained attention to the study of individual success predictions [3,4] and found that not only are the key factors affecting effective learning of mathematics but also interacting with some factors that influence mathematics learning in the mediation effect [5,6]. However, these findings have a lack of linkage between how the growth mindset influences in the same effect as variables that often influence mathematical learning results.…”
Section: Introductionmentioning
confidence: 99%